INCORPORATING CRITICAL LITERACY IN ELT: IMPROVING INDONESIAN STUDENTS’ CRITICAL THINKING AND WRITING ENGAGEMENT - Mahardika, Agustine Andriana Ayu; Silalahi, Ronald Maraden Parlindungan (Universitas Bunda Mulia, 2025)
This research investigates how critical literacy is applied in an English Language Teaching (ELT) context and how it promotes students’ critical thinking, engagement, and writing expression. Employing a qualitative case study approach, the researchers converged data through observation and semi-structured interviews with four participants from a private university in North Jakarta. It is shown that critical literacy guides students to examine social and political topics from various points of view, improves their classroom engagement, and assists the growth of organized and logical written arguments. Instead of simply emphasizing on enhancing writing details, this research focuses the function of critical literacy as a pedagogical approach that enable students to think intensely, communicate convincingly, and captivate with real-world topics in meaningful ways.